Distribution of water masses and diapycnal mixing in the Cape Verde Frontal Zone - Martínez-Marrero, A.; Rodríguez-Santana, A.; Hernandez-Guerra, Alonso; Fraile Nuez, Eugenio; López Laatzen, F.; Vélez Belchí, Pedro; Parrilla Barrera, Gregorio (Geophysical Research Letters, 2015)
The Cape Verde Frontal Zone separates North and South Atlantic Central Waters in the eastern North Atlantic Subtropical Gyre. CTD-O2 and shipboard ADCP data from three hydrographic sections carried out in September 2003 are used to study the structure of the front. Results show the relation between spatial variations of water masses and currents, demonstrating the importance of advection in the distribution of water masses. Diapycnal diffusivities due to double diffusion and vertical shear instabilities are also estimated. Existence of competition between the two processes through the water column is shown. Depth-averaged diffusivities suggest that salt fingering dominates diapycnal mixing, except areas of purest South Atlantic Central Water. Here, double diffusion processes are weak and, consequently, shear of the flow is the main process. Results also show that strong mixing induced by vertical shear is associated with a large intrusion found near the front. 2,959 Q1 SCIE